PEDAGOGICAL USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN EDUCATION - Cuentas Ávila, Dayanna
The article aimed to describe the pedagogical use of ICT in education. To do this, the qualitative paradigm was used with a type of descriptive research and bibliographic documentary design, applying hermeneutics for the interpretation of the results. Among the main findings, ICT must be used as didactic resources in the education process, it favors the acquisition of learning, thanks to the fact that students are willing to interact with the tools they use daily. It is concluded that the use of information and communication technologies facilitate the learning process, enable the intervention of students in the classroom, and make learning meaningful.